2019
DOI: 10.1093/trstmh/trz039
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-seeking behavior and practices among caregivers of children aged ≤5 y with presumed malaria in rural Uganda

Abstract: Background We aimed to determine the rate of herbal medicine usage and the treatment-seeking patterns of children aged ≤5 y with presumed or confirmed malaria in an endemic area of Uganda. Methods We interviewed guardians of 722 children aged 6 months to 5 y, who had experienced an episode of presumed malaria in the previous 3 months, about the illness history. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Despite their popularity, many drug shops are unlicensed or operated by vendors who lack the qualifications required by the National Drug Authority [7][8][9]. Drug shop vendors do not always have formal training in malaria case management [10] or provide treatment in accordance with national guidelines [5,7,[9][10][11][12]. Perhaps most critically, not all clients receiving antimalarials from drug shops have a confirmed malaria diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their popularity, many drug shops are unlicensed or operated by vendors who lack the qualifications required by the National Drug Authority [7][8][9]. Drug shop vendors do not always have formal training in malaria case management [10] or provide treatment in accordance with national guidelines [5,7,[9][10][11][12]. Perhaps most critically, not all clients receiving antimalarials from drug shops have a confirmed malaria diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…While RDT use in public facilities in Uganda is high, with an estimated diagnostic testing coverage of 84% [1], RDTs remain underused in the private sector. Previous studies found only 10 to 30% of clients treated for malaria at drug shops received an RDT [11][12][13]. Even when RDTs are used at the drug shop, clients often purchase antimalarials despite a negative result [13].…”
Section: Introductionmentioning
confidence: 99%
“…A similar study in Uganda also found that modern health care was more sought than herbal medicine. 30 Several factors affect treatment seeking behaviors of traditional medicine users like perceived efficacy, safety, age, availability of modern medicine, and cost. 9 In another study in Mali, respondents preferred a modern health facility when they had malaria.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study looking at dyspepsia in this region found that out of nine randomly selected health centers in the Namutumba District, none of the health centers had the capacity to test for H. pylori, and only two of the nine health centers prescribed appropriate triple therapy for clinically significant dyspepsia [ 14 ]. Moreover, unlicensed pharmacies provide approximately 40% of all healthcare to people in the Namutumba District [ 57 ]. Though diagnostic kits for H. pylori are relatively inexpensive [ 37 ], instituting government-level policies to make these tests widely available and providing a standard of care for management of dyspeptic patients prior to empiric antibiotic usage would be a more effective method to appropriately manage H. pylori infection and limit antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%